Предмет: Алгебра,
автор: Danmaner
Помогите тут легко))))))))))))))))))))))))))))))))))))))))
Приложения:
Ответы
Автор ответа:
0
1,8x - 2,3x² = - (2,4x² - 1,2x)
1,8x - 2,3x² + 2,4x² - 1,2x = 0
0,1x² + 0,6x = 0
x(0,1x + 0,6) = 0
x₁ = 0 0,1x + 0,6 = 0
0,1x = - 0,6
x₂ = - 6
Ответ: - 6
1,8x - 2,3x² + 2,4x² - 1,2x = 0
0,1x² + 0,6x = 0
x(0,1x + 0,6) = 0
x₁ = 0 0,1x + 0,6 = 0
0,1x = - 0,6
x₂ = - 6
Ответ: - 6
Похожие вопросы
Предмет: Информатика,
автор: yanamenshikova2
Предмет: Геометрия,
автор: drastamath
Предмет: Литература,
автор: egorvyatkin0703
Предмет: История,
автор: Kate589
Предмет: Литература,
автор: sklyarenkoegor